Precision Forming Process Analysis and Forming Process Simulation of Integrated Structural Gear for New Energy Vehicles - Zhang, Liyong; Zheng, Tianle; Li, Tongjie; Wang, Juan; Wang, Changlu; Jiang, Yehu; Li, Chengyu; Yuan, Fengxia; Yao, Zhihua (Manufacturing Technology Journal, 2023)
New energy vehicles driven by electric motors have higher requirements for the lightweight and high reliability of their gear transmission devices. It is now necessary to optimize the precision forming process of their structural gears. The integrated structure gear without undercut produced by precision forming technology can reduce axial size while improving the strength and reliability of gear parts. Based on the performance requirements of integrated structural gear parts in practical applications, a process plan of "hot forging forming +cold trimming tooth shape" was developed, and compared with existing hot extrusion forming plans. Simulation analysis was conducted on the hot forging forming process of integrated structural gears. Through the improvement and optimization of the process plan, the extrusion stress during the filling process of the formed gear teeth was reduced by about 29%, achieving a good forming effect, in order to provide data reference for the forming of this type of gear.
Keywords: Gear forming; Precision forming; Cold extrusion; Simulation analysis; Extrusion stress